Human papillomavirus‐related high‐grade squamous intraepithelial lesions of the esophagus, skin, and cervix in an adolescent lung transplant recipient: a case report and literature review. Issue 1 (24th December 2014) - Freiberger, D.; Lewis, L.; Helfand, L.
Abstract High‐risk (carcinogenic) genotype human papillomavirus (HPV) infections can be associated with significant morbidity in the immunocompromised solid organ transplant (SOT) recipient. Immunosuppression‐associated persistent infection can predispose to the development of rapidly progressive high‐grade squamous intraepithelial lesions (HSIL) in this population. We present a case report of an adolescent bilateral lung transplant recipient who developed HSIL of the esophagus, cervix, and skin secondary to HPV. This review highlights the unique developmental needs of the sexually active adolescent SOT recipient and reviews guidelines for HPV‐related screening and education of this population.